Higher Inflammatory Markers are correlated with Worse Cognitive Function in Coronavirus Disease-2019 Patients - Fitri, Fasihah Irfani; Darman, Winda Rahmah; Ritarwan, Kiking (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: This study aimed to determine the correlation between inflammation with cognitive function in COVID-19 patients. METHODS: We recruited COVID-19 patients using consecutive sampling methods in Adam Malik General Hospital Medan, Indonesia. The neutrophil-to-lymphocyte ratio (NLR,) C-reactive protein (CRP), D-dimer, and ferritin serum levels were measured as inflammatory markers . Cognitive function was assessed in several cognitive domains using Forward Digit Span for attention, Bacward Digit Span for working memory, and Trail Making Test parts A and B for executive function. The correlation between inflammatory markers and cognitive function was analyzed using Spearman correlation test. RESULTS: This study involved 40 COVID-19 patients consisting of 13 (32.5%) males and 27 (67.5%) females; the median age of the patients was 39.5 (19–65) years. We found that higher D-dimer and ferritin levels were significantly correlated with worse BDS scores (r = −0.369 p = 0.019 and r = −0.408 p = 0.009, respectively) and higher ferritin level was also correlated with worse FDS score (r = −0.365 p = 0.020 and). Higher D-dimer and ferritin levels were also significantly correlated with a longer time of completion of TMT-B (r = 0.363 p = 0.022 and r = 0.433 p = 0.005) and higher ferritin level was also correlated with a longer time of completion of TMT-A (r = 0.438 P=0.005). There were no significant correlations between NLR and CRP levels with cognitive function. CONCLUSION: Higher inflammatory markers are correlated with worse attention, working memory, and executive function in COVID-19 patients.